Adsorption of polyacrilic acid onto aluminium oxide and silicon carbide = Adsorpcija poliakrilne kiseline na aluminijevu oksidu i silicijevu karbidu : Doctoral Disertation - Marković, Berislav, kemičar; Somasundaran, Ponisseril; Ćosović, Božena; Kallay, Nikola; Veksli, Zorica (Zagreb : B. Marković, 1996)
Polymer adsorption at solid/liquid interface is influenced by various polymer, substrate and solution properties. In order to obtain a full insight into the kinetics and equilibrium of polymer adsorption process, a thorough investigation of these properties is needed. For this study, three different alumina samples were chosen as substrate. Adsorption of polyacrilic acide was investigated also on silicon carbide platelets. The characterization of powder materials used has shown: - Scanning Electron Microscopy observation have revealed the hard, highly porous agglomerates of Linde A and Aldrich aluminas. Sumitomo AKP50 alumina sample consists of isolated, nonporous particles of uniform size. Silicon carbide platelets are very smooth with wide size distribution.
Energy Dispersive X-ray Spectometry of silicon carbide platelets has shown the presence of oxygen, probably as a surface Si-O or Si-OH groups. - X.ray Diffraction patterns of Sumitomo AKP50 and Line A aluminas, did not show the presence of any phase other than [alfa]-Al2O3. - Particle size measurements using three different methods (Photon Correlation Spectrscopy, Forward Light Scattering Image Analysis) have given the following results for mean particle size values (diameter): Sumitomo AKP50: 0,267 [micro]m Linde A: 19,9[micro]m Aldrich Corundum: 73.3[micro]m Silicon Carbide 13.6[micro]m The particle was also determined for all materials. - Surface change (zeta potential) of alumina samples has shown similar behavior with iso-electric point of 8.9 and 8.4 for Sumutomo and Linde alumina respactively.
The change of silicon carbide platelets was measured using Electrokinetic Sonic Amplitude: the particles carry negative change throught the wide pH range with an iso-electric point at pH 3.2. - Specific surface area was measured using nitrogen adsorption (B.E.T. method) and the results have been calculated as: Sumitomo AKP50: 11.01m2/g Linde A: 14.52 m2/g Aldrich Corundum 9.62m2/g Silicon Carbide 0.49m2/g - Porosity of Linde A alumina was mesured using nitrogen adsorption and mercury intrusion porosiometry. The results have shown distinctive maxima for pore diameters of: 27, 55, 91, 200, 2000 and 40000 A.
The molecular size of polyacrylic acid was calculated for different molecular weight polymers in coiled (pH 4) and stretched (pH 10) conformations assuming no influence of electrostatic forces at low pH and no steric interactions between polymer segments at high pH. The study of polymer adsorption kinetics has shown that all the polymer was adsorbed at the alumina surface within an hour of mixing time (Linde A alumina, PAA Mw=5000, Cpaa=500ppm, pH). Hence, all further adsorption experiments were conducted using two hours of mixing time after polymer addition. A decrease of polymer adsorption density was observed with increasing pH of slurry. A significant amount of adsorbed polymer was observed even at pH at which alumina particles are negatively changed (pH higher than iso-electronic point).
This can be explained by surface inhomogeneity and possible formation of hydrogen bond between polymer and alumina surface group. The effect of slurry density (solid loading) was also investigated: a significant increase of adsorption density of polyacrylic acid on alumina was observed when solid loading was 25 and 50%. The reason can be in the fractionation of polydispersed polymer and/or in the interaction of polymer in solution with higher concentration of aluminum ions. The iso-electric point of minerals is shifted towards lower pH values by the addition of polymer. The decrease of zeta potential of particles was observed after polymer adsorption at pH below the iso-electric point, while the increase of negative change was measured at higher pH. The adsorption of fully ionized polymer makes negatively changed alumina even more negative.
The adsorption density plateau is found to increase with increase in polymer molecular weight due to the increase of adsorbed layer thickness at the Sumitomo AKP50 alumina surface. As the polymer molecular weight increase, the larger part of the adsorbed polymer molecules will be in the form of loops, causing the increase of adsorbed layer thickeness. In contrast, a decrease of adsorption was observed when higher molecular weight polymer was adsorbed on Linde A alumina. When the adsorption was conducted at high suspension pH, the adsorption was independent of polymer molecular weight.
The correlation of polymer molecular size and the pore size distribution of Linde A alumina has shown that the porous alumina surface acts as a selective filter for molecules of different sizes: smaller molecules can penetrate into the pores and the available surface area for polymer adsorptin is higher. However, the stretchedpolymer molecules at high pH can reach and adsorb on all the particle surface. Polyacrylic acid can adsorb on silicon carbide platelets only at low pH, when the particles are positive or of very low negative surface change. Therefore, the effect of pH on the adsorptin could not be studied. The effect of polymer molecular weight on adsorptin was found to be similar to that obtained on Sumitomo alumina: increase in adsorptin density with increasing polymer molecular weight.
Both these materials have smooth and nonporous particles and the increase of the adsorbed layer may be expected for the larger polymer molecules. This adsorptin makes the particles negative throught the investigated pH range (2 -11) and it is expected that positively changed alumina particles can be deposited on the silicon carbide platelets after pre-adsorptin of polyacrylic acide at low pH. The results of the extensive study of polyacrylic acid adsorption on the aluminas of different particle morphology have shown the direct correlation of polymer molecular weight (the size of plymer molecules) and the particle pore size distribution. This phenomenon is observed only at low pH, when polymer molecules are in colied conformation.
At high suspension pH, polymer molecules are streched and the maximum surface concentration is independent of polymer molecular weight. Interestingly, the adsorption of polyacrylic acide was observed also at pH higher than that of iso-electric point of alumina. The adsorption of polyacrylic acide was investigated also on silicon carbide platelets. The surface change of platelets can be changed by polymer adsorption. The findings of this study can provide not only the valuable information to better undrstand the relationship between the particle morphology and the polymer adsorption processes but also have shown the possibility of the deposition of one important ceramic material (alumina) on the modifed surface of the other (silicon carbide).
Sažetak: Fizikalno-kemijska svojstva polimera, substrata i općenito suspenzija određuju adsorpciju polimera na granici faza čvrsto/tekuće. Kako bi se dobio potpun uvid u kinetiku i ravnotežu adsorpcijskih procesa, potrebno je temeljito istražiti sva ta svojstva. Tri različita uzroka aluminijevog oksida su odabrana za ovaj rad. Adsorpcija poliakrilne kiseline je ispitana i na pločicama silicijevog karbida. Određena su svojstva praškastog materijala, kao što slijedi: - Čvrste, prozirne nakupine sastavljene od sitnih kristala u uzorcima aluminijevog oksida Linde A i Aldrich su dokazane primjenom pretražnog elektronskog mikroskopa (SEM). Uzorak aluminijevog oksida Sumitomo AKP50 imao je izolirane i neporozne čestice podjednakih veličina. Pločice silicijevog karbida bile su različitih veličina i vrlo glatke.
Spektroskopija energije raspršenih rentgenskih zraka je pokazala prisutnost kisika na silicijevom karbidu vjerojatno zbog površinskih Si-O ili Si-OH skupina. - Difrakcija rentgenskih zraka je pokazala prisutnost samo jedne kristalne faze ([alfa]-Al1O3) u uzorcima Linde A i Sumitomo AKP50. - Mjerenja veličine čestica korištenjem različitih metoda dala su slijedeće srednje vrijednosti za promjer Čestica: Sumitomo AKP50: 0,269[mikro]m Linde A: 19,9[mikro]m Korund Aldrich: 73,3[mikro]m Silicijev karbid: 13,6[mikro]m Distribucija veličine čestica također je određena za sve materijale. - Naboj površine (zeta potencijal) je sličan za obadva uzorka aluminijevog oksida, Sumitomo AKP50 i Linde A, a njihova izoelektrična točka je 8,9 odnosno 8,4. Naboj pločica silicijevog karbida određen je mjerenjem elektrokinetičke zvučne amplitude (ESA)
čestice su negativnog naboja u širokom pH području s izoelektričnom točkom kod pH 3,2. - Specifična površina je određena adsorpcijom dušika (metoda B.E.T.), a dobiveni su slijedeći rezultati: Sumitomo AKP50: 11,01m2/g Linde A: 14,52m2/g Korznd Aldrich: 9,62m2/g Silicijev karbid: 0,49m2/g - Pozornost aluminijevog oksida Linde A određena je adsorpcija dušika i živinom porozimetrijom. Pokazalo se da postoje maksimumi za veličinu pora promjera 27, 55, 91, 200, 2000 i 40000 A. Veličina molekila poliakrilne kiseline je izračunata za različite molarne mase u slučaju kada je polimer u zavijenoj (colied) i ispruženoj (streched) konformaciji. U računu je pretpostavljeno da nema utjecaja elektrostatskih sila kod niskog pH niti steričkih interakcija kod visokog pH.
Određivanjem kinetike adsorpcije polimera je ustanovljeno da je do potpune adsorpcije došlo unutar jednog sata. Na osnovi ovog rezultata, svi adsorpcijski eksperimenti su provedeni uz miješanje od dva sata. Povišenje lužavosti sustema dovodi do smanjene adsorpcije poliakrilne kiseline iako je značajna količina polimera adsorbira i u području pH kada su čestice aluminijevog oksida negativnog naboja (pH iznad izoelektroničke točke). Utjecaj udjela čvrste tvari u suspenziji na adsorpciju je također ispitan. Značajan porast adsorbirane količine polimera izmjeren je u suspenzijama s 25 odnosno 50% čvrste tvari. Uzrak tomu mogu biti frakcijska adsorpcija polimera uslijed njegove polidisperzivnosti i/ili reakcije s ionima aluminija u otopini. Adsorpcija polimera dovodi do pomaka izoelektrične točke prema nižem pH.
Zeta potencijal čestice se smanjuje adsorpcijom polimera u pH području ispod izoelektrične točke dok je kod visokog pH zapažen porast negativnog potencijala. To znači da već negativni aluminijev oksid postaje još i više negativan zbog adsopcije potpuno ioniziranog polimera. Adsorpcijski maksimum raste proporcionalno s porastom molekulske mase polimera adsorbiranog na uzorku Sumitomo AKP50. Taj se porast može pripisati povećanju debljine adsorbiranog sloja polimera. Kod adsorpcije većih molekula polimera (veća molekulska masa), sve veći dio molekule se nalazi u petljama ("loops"), te se samim time povećava i debljina adsorbiranog sloja. Neuobičajeno opadanje adsorpcijskog maksimuma s porastom molekulske mase polimera uočeno je u slučaju materijala Linde A.
Porastom pH sistema, razlike u adsoepcijskim maksimumima za različite molekulske mase polimera se amanjuju i gotvo nestaju pri pH 10. Usporedba veličina molekula polimera s raspodjelom veličina pora na česticama aluminijevog oksida Linde A pokazuje da površina čestica djeluje kao svojevrstan filter; malene molekule mogu ući u unutrašnjost pora i raspoloživa površina za adsorpciju je povećana. Kod visokog pH, molekule polimera su ispružene i mogu biti adsrobirane na cijeloj površini čestica. Do adsorpcije poliakrilne kiseline na pločicama silicijevog karbida dolazi jedino pri niskom pH kada su one nabijene pozitivno ili vrlo slabo negativno. Ispitivanje utjecaja molekulske mase polimera na adsorpciju pokazalo je slične rezulatate kao i kod aluminijevog oksida Sumitomo: porastom molekulske mase polimera, raste i maksimalna površinska koncentracija.
Iako mahanizam adsorpcijskih procesa na različitim materijalima može biti različite prirode, povećanje debljine adsorbiranog sloja se može očekivati kod adsorpcije na glatkim i neporoznim površinama. Nakon adsorpcije, pločice poprimaju nagativni naboj unutar širokog pH područja (2-11) te je za očekivati mogućnost taloženja pozitivno nabijenih čestica alumonijevog oksida na njima. Usporedba rezultata adsorpcijskih mjerenja sa mikrološkim karakteristikama ispitivanih aluminijevih oksida pokazala je direktnu međuzavisnost molekulske mase polimera (veličine molekula) sa raspodjelom veličine pora čestica. Takva korelacija vrijedi samo onda kada su molekule polimera u "coiled" konformaciji.
Ispružene molekule ("streched, pri visokom pH) se mogu slobodnije kretati unutar pora, pa su maksimalne površinske koncentracije neovisne o molekulskoj masi polimera. Nasuprot nekim prethodno objavljenim rezultatima, poliakrilna kiselina se adsorbira na aluminijevom oksidu i pri pH višem od izoelektrične točke. Adsorpcija poliakrilne kiseline ispitivana je i na pločicama silicijevog karbida te se je pokazalo da dolazi do promjene površinskog naboja nakon adsorpcije. Budući da su i aluminijev oksid i silicijev karbid važni keramički materijal, rezultati ovog rada trebali bi poslužiti ne samo kao doprinos poznavanju adsorpcijskih procesa na proznim i neporoznim materijalima, već i kao osnova za razvoj tehnike pripreme različitih karamika na osnovama koloidne kemije.
Doktor prirodnih znanosti - kemija
Mentror: Ponisseril Somasundaran; Komisija za ocjenu: Božena Ćosović, Ponisseril Somasundaran, Nikola Kallay, Zorica Veksli
Sveučilište u Zagrebu, Prirodoslovno-matematički fakultet, Zagreb, 1996
Bibliografija: str. 105-110
Sažetak
Keywords: Polimeri -- Porozitet čestica